Understanding the differential performance in hygienic behavior against dead brood of drones and workers of Apis mellifera : a chemical approach - Duggan Dowd, Delfina; Muntaabski, Irina; Russo, Romina Maria; Galindo Cardona, Alberto; Scannapieco, Alejandra Carla; Liendo, María Clara (Taylor and Francis, 2025)
Hygienic behavior is a social health mechanism displayed by honey bee workers of Apis mellifera by which dead or diseased brood is removed from the hive. Such behavior is known to be induced by olfactory cues. The efficiency of hygienic behavior toward drone brood cells is significantly lower than that of worker brood cells. A possible explanation for this difference lies in the cell wax cap of drone brood, which may act as a barrier to the diffusion of characteristic odors associated with diseased brood. The aim of this research was to explore the importance of drone cell wax cap as an interfering factor in the diffusion of chemical signals within honey bee colonies. To this end, brood removal percentages were compared among several types of brood: pin-killed worker, pin-killed drone, pin-killed worker with a healthy drone wax cap, healthy worker with a pin-killed drone wax cap, and healthy worker covered with a healthy drone wax cap. Results showed that the removal behavior did not differ between cells with pin-killed worker and pin-killed worker with a healthy drone wax cap, but was significantly higher towards healthy worker pupae covered with dead drone wax cap compared to the negative control (healthy worker pupa covered with a healthy drone cell wax cap). Present evidence suggests that chemical signals associated with the dead drone brood would be less volatile and retained to some extent in the wax cap, and partially explain the differential hygienic behavior between both types of brood.